Moralitas dan Kewajiban: Pemikiran Etis Emanuel Kant - Buran, Silverius Felix; Hayon, Bernadus Suban (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
Morality and duty are two central concepts in the ethical thought of Emanuel Kant, a German philosopher who was influential in the history of Western philosophy. Within his deontological ethical framework, Kant emphasized the importance of moral action based on rational and universal principles. He argued that morality does not depend on the consequences of actions, but on the intention and obligation to obey the generally applicable moral law. In his work "Groundwork for the Metaphysics of Morals", Kant introduced the categorical imperative as a primary principle that requires individuals to act only in accordance with intentions that can be made into universal laws. This concept emphasizes that right actions are those that are rationally acceptable and apply to everyone without exception. Through an in-depth analysis of morality and duty, Kant's thought provides a foundation for an understanding of ethics that focuses on justice and respect for human dignity. This abstract aims to explore the implications of Kant's thought in the context of contemporary morality and the challenges faced in applying his ethical principles in everyday life.